Crossroads of the Atlantic: Portugal, the Azores and the Atlantic Community (1943-57) - Rodrigues, L. N. (European Community, Atlantic Community?, 2008)
There is an evident paradox in the participation of Portugal in the emerging Atlantic Community after World War II, at least if we identify this commu- nity with the political and military alliance de ned by the North Atlantic Treaty Organization, and with the transatlantic economic cooperation as set in motion by the Marshall Plan. NATO, for instance, was created by its mem- ber states to “safeguard the freedom, common heritage and civilisation of their peoples, founded on the principles of democracy, individual liberty and the rule of law.”1 Yet, among its founding members we can nd a country like Portugal, living under a right-wing authoritarian regime and led by the same prime-minister—Oliveira Salazar—since 1932.